Heavy-duty steel plate, structure, and method for manufacturing heavy-duty steel plate
Patent Information
- Application Number
- JP2023033160
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-07
- Filing Date
- 2023-03-03
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2043-03-03
AI Technical Summary
【0022】 本発明によれば、高強度であり、全厚での伸び特性、耐疲労き裂伝播特性、靭性および塗装耐久性に優れた厚鋼板および構造物を得ることができる。本発明の厚鋼板では、仮に応力集中部や溶接部等から疲労き裂が経年的に発生したとしても、その後のき裂の伝播が抑制されるため、鋼構造物全体の安全性を高めることが可能である。また、本発明によれば、屋外の大気腐食環境下、特には飛来塩分量の多い海上や海岸近傍などの厳しい腐食環境下で使用する場合であっても、塗り替え周期を延長して塗装頻度を低減することが可能な塗装耐久性に優れた厚鋼板を、低コストに得ることができる。
Smart Images

Figure 0007635794000005 
Figure 0007635794000001 
Figure 0007635794000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a thick steel plate and a manufacturing method thereof, and in particular to a thick steel plate excellent in elongation characteristics across the entire thickness, fatigue crack propagation resistance, and toughness, and a manufacturing method thereof. The thick steel plate of the present invention can be suitably used for welded structures where structural safety is highly required, such as ships, marine structures, bridges, buildings, and tanks. The present invention also relates to structures, such as bridges, that are used in outdoor atmospheric corrosive environments, particularly in severe corrosive environments such as on the sea or near the coast where there is a large amount of airborne salt. [Background technology]
[0002] Heavy steel plates are widely used in structures such as ships, marine structures, bridges, buildings, tanks, etc. Such heavy steel plates are required to have excellent mechanical properties such as strength and toughness, as well as excellent weldability, and also excellent fatigue resistance.
[0003] When such a structure is used, the structure is subjected to repeated loads such as vibrations caused by wind and earthquakes, etc. Therefore, the thick steel plate is required to have durability against ductile fracture, brittle fracture, and fatigue fracture in order to ensure the safety of the structure even when such repeated loads are applied.
[0004] Ductile fracture is an event in which tiny voids are generated and connected under static stress with a small strain rate, leading to the breakage of a material. Resistance to ductile fracture can be improved by increasing the yield stress, tensile strength, and elongation, which are quantified by tensile tests.
[0005] Brittle fracture is an event in which a material breaks due to an impact force with a large strain rate without any prior signs of damage such as deformation. Resistance to brittle fracture can be improved by increasing the toughness value, which is quantified in the Charpy impact test. It is generally known that toughness decreases inversely with increasing strength and plate thickness.
[0006] Fatigue fracture is a phenomenon in which a tiny crack (fatigue crack) first occurs, and then the crack spreads (progresses). In most cases, fatigue cracks occur at welds, propagate through the steel, and eventually destroy the steel. This is believed to be due to the fact that welds tend to become stress concentration areas due to their shape, and also because tensile residual stress occurs after welding. For this reason, techniques such as peening that introduce compressive residual stress are widely known as a means of suppressing crack generation from welds.
[0007] However, it is not realistic to apply such treatment to all of the many welds present in a structure in terms of workability and manufacturing costs. Therefore, even if a fatigue crack initiates from a weld, it is important to extend the fatigue life of the welded structure by delaying the subsequent propagation of the crack in the steel material, and it is therefore desirable to improve the fatigue crack propagation resistance of the steel material itself.
[0008] For example, Patent Document 1 proposes a thick steel plate in which, in order to improve excellent fatigue crack propagation resistance and elongation characteristics throughout the entire thickness, the microstructure in the thickness direction from the surface to 100 μm below the surface contains ferrite phase in an area ratio of 80% or more, and the microstructure in the range from 100 μm below the surface to 1 / 2 the plate thickness position contains ferrite phase in an area ratio of 80% or less, with the remainder being pearlite phase, bainite phase, or a mixed phase of pearlite phase and bainite phase.
[0009] Meanwhile, steel structures used outdoors, such as bridges, are usually subjected to some kind of anti-corrosion treatment before use. For example, weathering steel is often used in environments with low levels of airborne salt. Weathering steel is a steel material whose surface is covered with a highly protective rust layer containing concentrated alloy elements such as Cu, P, Cr, and Ni when used in an atmospheric exposure environment, thereby significantly reducing the corrosion rate. It is known that bridges using such weathering steel can withstand decades of use without painting in environments with low levels of airborne salt.
[0010] On the other hand, in environments with high levels of airborne salt, such as at sea or near the coast, it is difficult for weathering steel to form a highly protective rust layer, making it difficult to use weathering steel without painting. For this reason, in environments with high levels of airborne salt, such as at sea or near the coast, painted steel, which is made by applying anticorrosion treatment such as painting to ordinary steel, is generally used.
[0011] However, painted steel requires periodic repairs such as repainting due to deterioration of the paint film over time, the occurrence of rust, and swelling of the paint film. The painting work required for repainting is often carried out at high altitudes, which is difficult and requires labor costs. Therefore, the use of painted steel increases the maintenance costs of the structure, which in turn increases the life cycle costs.
[0012] For these reasons, there is a need for the development of steel materials with excellent corrosion resistance, in particular structural steel materials with excellent paint durability, that can extend the repainting cycle, thereby reducing the frequency of painting and reducing the maintenance costs of structures.
[0013] Patent Document 2 discloses a steel material for painting that contains 0.05 to 3.0% Cu, 0.05 to 6.0% Ni, and 0.025 to 0.15% Ti and has excellent paint film durability.
[0014] Patent Document 3 discloses a steel material having excellent corrosion resistance that contains more than 1.0 to 13.0% Cr and 0.01 to 0.5% Sn. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] JP 2019-026927 A [Patent Document 2] JP 2000-169939 A [Patent Document 3] JP 2013-166992 A Summary of the Invention [Problem to be solved by the invention]
[0016] However, the conventional technology described in Patent Document 1 has the following problems. In Patent Document 1, the reheated hot-rolled sheet is cooled at an average cooling rate of 3 to 20°C / s and quenched. In this method, no attention is paid to the toughness value, and the toughness value may decrease because the bainite phase may be formed more predominantly than the pearlite phase and island martensite exists in the bainite phase. In addition, the weather resistance of the steel material proposed in Patent Document 1 is insufficient.
[0017] On the other hand, if alloy elements such as Cr and Sn are excessively contained along with Cu and Ni as in Patent Documents 2 and 3 for the purpose of improving weather resistance, not only does the alloy cost increase but also toughness deteriorates.
[0018] As described above, conventional manufacturing methods had the problem that it was not possible to manufacture thick steel plates that had all of the following properties: elongation through thickness (also called elongation through thickness), fatigue crack propagation resistance, toughness, and coating durability.
[0019] The present invention has been made in consideration of the above circumstances, and has an object to provide a thick steel plate with excellent paint durability that has high strength, excellent elongation characteristics across its entire thickness, excellent fatigue crack propagation resistance, and toughness, and does not require the inclusion of large amounts of expensive Cu, Ni, or Cr, thereby preventing an excessive increase in alloy costs, and that can extend the cycle for repainting and reduce the frequency of painting even when used in outdoor atmospheric corrosive environments such as bridges, particularly in severe corrosive environments such as at sea or near coasts with a high amount of airborne salt, as well as a manufacturing method and structure thereof. [Means for solving the problem]
[0020] As a result of investigations conducted by the present inventors to solve the above problems, the present inventors have obtained the following findings. (1) After hot rolling and cooling, the steel plate has a variation in structure in the rolling direction (longitudinal direction) due to the deviation in the cooling stop temperature. However, by reheating to a temperature range above Ac3 (first reheating step), not only can the variation in structure due to the deviation in the cooling stop temperature after hot rolling be eliminated, but the ferrite phase inside the plate thickness after cooling can be refined, improving toughness. (2) By reheating (second reheating process) to a temperature in the Ac1 temperature range (two-phase region) or higher after the first reheating process, ferrite is generated in the surface layer, improving the elongation characteristics. (3) By providing cooling after the second reheating step, the ferrite phase in the plate thickness interior is further refined, and the toughness is further improved. (4) Even when the plate thickness is thin, by controlling the cooling pattern after the second reheating process, it is possible to achieve both high strength over the entire length and good elongation characteristics and fatigue crack propagation resistance over the entire thickness. (5) In the cooling pattern after the second reheating step, the cooling rate is appropriately controlled to generate more pearlite phase than bainite phase, thereby further improving the toughness. (6) The inclusion of W significantly suppresses the formation of rust under the paint film, and is effective in preventing paint film blistering and peeling.
[0021] The present invention has been made based on the above findings, and has the following gist and configuration. [1] In weight percent: C: 0.05-0.20%, Si: 0.01 to 0.50%, Mn: 0.50-2.00%, P: 0.05% or less, S: 0.02% or less, W: 0.005~1.00% and Sn: 0.005~0.500%, Sb: Contains at least one of 0.005 to 0.200%; The balance is composed of Fe and unavoidable impurities, The microstructure is In the thickness direction, the area from the surface to 100 μm below the surface contains ferrite phase of 80% or more by area ratio, and At 1 / 4 of the plate thickness, Contains a ferrite phase having an area ratio of 90% or less and an average grain size of 25 μm or less, The remainder of the steel plate is a hard phase, the hard phase being dispersed in a ferrite phase, the hard phase including a pearlite phase, and the average spacing between the hard phases being less than 25 μm. [2] The composition further comprises, in mass%, Cu: 0.01 to 1.00%, Ni: 0.01 to 1.00%, Cr: 0.01 to 1.00%, Mo: 0.01 to 1.00%, V: 0.005~0.100%, Ti: 0.005 to 0.10%, B: 0.0001~0.0050%, Ca: 0.0001 to 0.020%, Mg: 0.0001 to 0.020%, and The steel plate according to [1], containing one or more selected from the group consisting of REM: 0.0001 to 0.020%. [3] A steel plate according to [1] or [2], wherein the hard phase is a pearlite phase or a mixed phase of pearlite and bainite, and the area ratio of the pearlite phase in the mixed phase is larger than the area ratio of the bainite phase. [4] The steel plate according to any one of [1] to [3], which has a coating film on a surface. [5] The coating film includes a corrosion-resistant undercoat layer, a primer layer, a midcoat layer and a topcoat layer, The thick steel plate according to [4], wherein the corrosion-resistant undercoat layer is made of inorganic zinc-rich paint, the undercoat layer is made of epoxy resin paint, the intermediate coat layer is made of intermediate paint for a fluororesin top coat paint, and the top coat layer is made of a fluororesin top coat paint. [6] A structure formed using the thick steel plate according to any one of [1] to [5] above. [7] The structure described in [6], wherein the structure is a bridge. [8] A heating step of heating a steel material having the composition according to the above [1] or [2] to 900 to 1200 ° C.; a rolling step of subjecting the steel material heated in the heating step to hot rolling at a cumulative rolling reduction rate of 50% or more to obtain a thick steel plate; A cooling step after the rolling step of cooling the thick steel plate; A first reheating step of reheating the steel plate cooled in the cooling step after the rolling step to a first reheating temperature of not less than the Ac3 transformation point and not more than 950 ° C.; A first cooling step of cooling the steel plate reheated in the first reheating step; A second reheating process in which the steel plate cooled in the first cooling process is reheated to a second reheating temperature of the Ac1 transformation point or higher and 950 ° C. or lower; A second cooling step of cooling the steel plate reheated in the second reheating step to a second cooling stop temperature of 350 to 600 ° C. at an average cooling rate of 1.5 to 20 ° C. / s; a water cooling process for water cooling the steel plate cooled in the second cooling process; A method for manufacturing a thick steel plate having the above structure. [9] The method for producing a steel plate according to [8], wherein the average cooling rate in the second cooling step is 1.5 to 7°C / s. Effect of the Invention
[0022] According to the present invention, it is possible to obtain a thick steel plate and a structure having high strength and excellent elongation characteristics in the entire thickness, fatigue crack propagation resistance, toughness, and paint durability. In the thick steel plate of the present invention, even if fatigue cracks occur over time from stress concentration parts, welded parts, etc., the subsequent crack propagation is suppressed, so that it is possible to improve the safety of the entire steel structure. Furthermore, according to the present invention, it is possible to obtain a thick steel plate having excellent paint durability at low cost, which allows the repainting cycle to be extended and the frequency of painting to be reduced, even when used in an outdoor atmospheric corrosive environment, particularly in a severe corrosive environment such as the sea or near the coast where there is a large amount of airborne salt. [Brief description of the drawings]
[0023] [Figure 1]FIG. 1 is a schematic diagram of a single-side notched simple tension fatigue test piece used in a fatigue crack propagation test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Next, a method for carrying out the present invention will be specifically described. Note that the following description shows a preferred embodiment of the present invention, and the present invention is not limited to the following description in any way.
[0025] [Component composition] The reasons for limiting the chemical composition of the steel plate of the present invention will be described below. In the following description, "%" refers to "mass %" unless otherwise specified.
[0026] C: 0.05 to 0.20% C is an element that has the effect of increasing the hardness of the matrix and improving the strength. In addition, C has the effect of generating a pearlite phase, which is an aggregate of cementite phases, and therefore the fatigue crack propagation resistance is improved. In order to obtain such an effect, it is necessary to make the C content 0.05% or more. The C content is preferably 0.08% or more, more preferably 0.10% or more, and even more preferably 0.12% or more. On the other hand, if the C content exceeds 0.20%, the hardness of the matrix phase increases excessively and the elongation in the total thickness deteriorates. For this reason, the C content is set to 0.20% or less. The C content is preferably 0.18% or less, more preferably 0.16% or less, and even more preferably 0.15% or less.
[0027] Silicon: 0.01 to 0.50% Si acts as a deoxidizer and is an element that dissolves in steel to increase the hardness of the matrix phase through solid solution strengthening, thereby improving strength. In order to obtain such an effect, the Si content must be 0.01% or more. The Si content is preferably 0.05% or more, more preferably 0.10% or more, even more preferably 0.15% or more, and most preferably 0.20% or more. On the other hand, if the Si content exceeds 0.50%, the elongation and toughness in the total thickness decrease. For this reason, the Si content is set to 0.50% or less. The Si content is preferably 0.45% or less, more preferably 0.40% or less, even more preferably 0.35% or less, and most preferably 0.30% or less.
[0028] Mn: 0.50-2.00% Mn is an element that has the effect of increasing the hardness of the matrix phase and improving the strength. In order to obtain such an effect, the Mn content must be 0.50% or more. The Mn content is preferably 0.60% or more, more preferably 0.70% or more, even more preferably 0.80% or more, and most preferably 1.00% or more. On the other hand, if the Mn content exceeds 2.00%, in addition to the weldability decreasing, the inclusion MnS segregates excessively and the toughness decreases. For this reason, the Mn content is set to 2.00% or less. The Mn content is preferably 1.85% or less, more preferably 1.70% or less, even more preferably 1.55% or less, and most preferably 1.40% or less.
[0029] P:0.05% or less P is an element contained in steel as an unavoidable impurity. Since P segregates at grain boundaries and has adverse effects such as reducing the toughness of the base material and welded parts, it is preferable to reduce it as much as possible, but a content of 0.05% or less is acceptable. For this reason, the P content is set to 0.05% or less. The P content is preferably 0.04% or less, and more preferably 0.03% or less. On the other hand, although there is no lower limit for the P content, an excessive reduction leads to an increase in refining costs, so the P content is preferably 0.001% or more. The P content is preferably 0.002% or more, and more preferably 0.003% or more.
[0030] S: 0.02% or less S is an element contained in steel as an unavoidable impurity. S exists in steel as sulfide-based inclusions such as MnS, and since it becomes the starting point of brittle fracture and deteriorates toughness, it is preferable to reduce it as much as possible, but a content of 0.02% or less is acceptable. For this reason, the S content is set to 0.02% or less. The S content is preferably set to 0.01% or less. On the other hand, although there is no lower limit for the S content, since excessive reduction leads to an increase in refining costs, the S content is preferably set to 0.0005% or more.
[0031] W: 0.005~1.00% W dissolves during the anodic reaction of the steel plate and is dissolved in the rust layer as WO4 2-By distributing as , it electrostatically prevents chloride ions, which are corrosion accelerating factors, from penetrating the rust layer and reaching the base steel. Furthermore, compounds containing W are precipitated on the surface of the thick steel plate, suppressing the anodic reaction of the thick steel plate. And, W, after adjusting the Si content to an appropriate range, is contained in combination with Sn, Sb, and further Cu and Ni, and the coating durability of the thick steel plate is greatly improved by the synergistic effect with these elements. In order to fully obtain such an effect, it is necessary to contain W at 0.005% or more. The W content is preferably 0.010% or more, more preferably 0.030% or more, and even more preferably 0.050%. On the other hand, if the W content exceeds 1.00%, the alloy cost increases. Therefore, the W content is 1.00% or less. Preferably, it is 0.70% or less, more preferably 0.50% or less, and even more preferably 0.30% or less.
[0032] At least one of Sn: 0.005-0.500%, Sb: 0.005-0.200% In the present invention, the coating durability of thick steel plate is improved by containing at least one of Sn and Sb.
[0033] Sn: 0.005 to 0.500% Sn is present in the rust layer near the surface of the base steel, and by refining the rust particles, it prevents chloride ions, which are corrosion-promoting factors, from penetrating the rust layer and reaching the base steel. Sn also suppresses the anodic reaction on the steel surface. When Sn is contained in combination with W, the synergistic effect of these elements greatly improves the paint durability of the thick steel plate. When Sn is contained, it is necessary to contain 0.005% or more of Sn in order to fully obtain the above-mentioned effect. The Sn content is preferably 0.010% or more, more preferably 0.020% or more. On the other hand, if the Sn content exceeds 0.500%, the ductility and toughness of the steel will deteriorate. Therefore, the Sn content is set to 0.500% or less. The Sn content is preferably 0.300% or less, more preferably 0.200% or less, and even more preferably less than 0.050%.
[0034] Sb: 0.005 to 0.200% Sb is present in the rust layer near the surface of the base steel, and by refining the rust particles, it prevents chloride ions, which are corrosion-promoting factors, from penetrating the rust layer and reaching the base steel. Sb also suppresses the anodic reaction on the surface of the thick steel plate. When Sb is contained in combination with W, the synergistic effect of these elements greatly improves the paint durability of the thick steel plate. When Sb is contained, it is necessary to contain 0.005% or more of Sb in order to fully obtain the above-mentioned effect. The Sb content is preferably 0.010% or more, more preferably 0.020% or more. On the other hand, if the Sb content exceeds 0.200%, the ductility and toughness of the steel will deteriorate. Therefore, the Sb content is set to 0.200% or less. The Sb content is preferably 0.150% or less, more preferably 0.100% or less.
[0035] The balance is composed of Fe and unavoidable impurities. If the content of oxygen (O) contained as an unavoidable impurity exceeds 0.0050%, the ratio of inclusions present on the steel sheet surface increases, so that cracks originating from the inclusions tend to occur. Therefore, the O content is preferably 0.0050% or less. Similarly, if the content of N contained as an unavoidable impurity exceeds 0.0050%, the ratio of inclusions present on the steel sheet surface increases, so that cracks originating from the inclusions tend to occur. Therefore, the N content is preferably 0.0050% or less. The N content is more preferably 0.0040% or less. Similarly, if the content of sol.Al contained as an unavoidable impurity exceeds 0.060%, Al is mixed into the weld metal during welding, and the toughness of the weld deteriorates. Therefore, the sol.Al content is preferably 0.060% or less. The sol.Al content is more preferably 0.050% or less, and further preferably 0.040% or less. The oxygen (O) content, sol.Al content and N content may be 0%.
[0036] In the present invention, at least one of the following elements may be optionally contained. By containing these optional elements, the properties of the steel plate, such as strength, toughness, weldability, weather resistance, and paint durability, can be further improved.
[0037] Cu: 0.01-1.00% Cu is an element that has the effect of further increasing strength through solid solution and improving weather resistance. In addition, Cu has the effect of suppressing the penetration of oxygen and chloride ions, which are corrosion-promoting factors, into the base steel by forming a dense rust layer. Cu, when contained together with W, further greatly improves the paint durability of the thick steel plate. When Cu is contained, the Cu content is set to 0.01% or more in order to obtain the above effect. The Cu content is preferably 0.04% or more. On the other hand, when the Cu content exceeds 1.00%, the weldability is impaired and defects are easily generated during the production of the thick steel plate. Therefore, when Cu is contained, it is set to 1.00% or less, preferably 0.70% or less, and more preferably 0.40% or less.
[0038] Ni: 0.01 to 1.00% Ni is an element that has the effect of improving low-temperature toughness, and improves hot brittleness when Cu is contained. Ni also has the effect of suppressing the penetration of oxygen and chloride ions, which are corrosion-promoting factors, into the base steel by forming a dense rust layer. Ni, when contained together with W, further greatly improves the paint durability of the thick steel plate. When Ni is contained, the Ni content is set to 0.01% or more in order to obtain the above effect. The Ni content is preferably 0.04% or more. On the other hand, when the Ni content exceeds 1.00%, the weldability is impaired and the steel cost increases. Therefore, when Ni is contained, it is set to 1.00% or less, preferably 0.70% or less, and more preferably 0.40% or less.
[0039] Cr: 0.01 to 1.00% Cr is an element that has the effect of improving strength. In addition, Cr is an element that promotes the formation of cementite, and promotes the formation of pearlite phase, which is advantageous for fatigue crack propagation resistance. When Cr is contained, in order to obtain the above effect, the Cr content is set to 0.01% or more, preferably 0.10% or more. On the other hand, when the Cr content exceeds 1.00%, weldability and toughness are impaired. Therefore, when Cr is contained, the Cr content is set to 1.00% or less. The Cr content is preferably set to 0.80% or less, more preferably 0.50% or less.
[0040] Mo: 0.01 to 1.00% Mo is an element that has the effect of increasing the hardness of the matrix phase and improving strength, and can be contained arbitrarily depending on the desired properties. When Mo is contained, the Mo content is set to 0.01% or more in order to obtain this effect. The Mo content is preferably set to 0.04% or more. However, if the Mo content exceeds 1.00%, the weldability and toughness are impaired, so if Mo is contained, the Mo content is set to 1.00% or less.
[0041] V: 0.005~0.100% V is an element that has the effect of suppressing the recrystallization of austenite during hot rolling to make the grains finer, and also of increasing the strength by precipitating during the air-cooling process after hot rolling, and can be contained arbitrarily according to the desired properties. In order to obtain the above effect, when V is contained, the V content is set to 0.005% or more. The V content is preferably set to 0.010% or more. However, when the V content exceeds 0.100%, a large amount of VC is precipitated, and the toughness is impaired. Therefore, when V is contained, the V content is set to 0.100% or less.
[0042] Ti: 0.005 to 0.10% Ti has a strong tendency to form nitrides, fixes N and reduces solute N, and therefore has the effect of improving the toughness of the base material and welded parts. In addition, when B is contained, Ti is also contained, so that Ti fixes N and B can be prevented from precipitating as BN. As a result, the hardenability improving effect of B is promoted, and the strength can be further improved. Therefore, it can be contained arbitrarily according to the desired characteristics. In order to obtain the above effect, when Ti is contained, it is set to 0.005% or more. The Ti content is preferably 0.01% or more. However, when the Ti content exceeds 0.10%, a large amount of TiC is precipitated, and the toughness is impaired. Therefore, when Ti is contained, the Ti content is set to 0.10% or less. The Ti content is preferably 0.05% or less.
[0043] B: 0.0001 to 0.0050% B is an element that has the effect of significantly improving hardenability and increasing strength even in small amounts, and can be contained according to the desired properties. In order to obtain the above effects, when B is contained, it is set to 0.0001% or more. The B content is preferably 0.0002% or more. However, when the B content exceeds 0.0050%, not only does the effect saturate, but also weldability is reduced, so when B is contained, the B content is set to 0.0050% or less. The B content is preferably 0.0030% or less.
[0044] Ca: 0.0001 to 0.020% Ca combines with S to suppress the formation of MnS and the like that elongates in the rolling direction, controls the shape of sulfide-based inclusions so that they are spherical, and contributes to improving the toughness of welds and the like, so it can be contained according to the desired properties. When Ca is contained, the Ca content is set to 0.0001% or more to obtain this effect. The Ca content is preferably 0.0004% or more. However, when the Ca content exceeds 0.020%, not only does the effect saturate, but the cleanliness of the steel decreases, surface defects occur frequently, and the surface properties deteriorate. For this reason, when Ca is contained, the Ca content is set to 0.020% or less. The Ca content is preferably 0.010% or less.
[0045] Mg: 0.0001 to 0.020% Mg is an element that has the effect of improving toughness through grain refinement. When Mg is contained, the Mg content is preferably 0.0001% or more in order to obtain the above effect. The Mg content is preferably 0.0004% or more. On the other hand, when the Mg content exceeds 0.020%, the effect is saturated. Therefore, when Mg is contained, the Mg content is 0.020% or less. The Mg content is preferably 0.010% or less.
[0046] REM: 0.0001~0.020% REM (rare earth metal) is an element that has the effect of improving toughness. When REM is contained, the REM content is set to 0.0001% or more in order to obtain the above effect. The REM content is preferably 0.0004% or more. On the other hand, when the REM content exceeds 0.020%, the effect is saturated. Therefore, when REM is contained, the REM content is set to 0.020% or less. The REM content is preferably 0.010% or less.
[0047] [Microstructure] Next, the reasons for limiting the microstructure of the steel plate will be described. Note that "%" in the description of the microstructure refers to the area ratio unless otherwise specified.
[0048] The structure from the surface to 100 μm below the surface (surface structure) In the steel plate of the present invention, the microstructure in the thickness direction from the surface to 100 μm below the surface (hereinafter, sometimes simply referred to as the "surface layer") contains 80% or more of ferrite phase in terms of area ratio. In the two-phase region between the Ac1 transformation point and the Ac3 transformation point, a surface decarburization reaction occurs, and 80% or more of ferrite phase is generated in the surface layer, softening the surface layer of the steel plate, thereby significantly improving the elongation characteristics in the entire thickness. This surface decarburization reaction occurs by passing through or holding in the two-phase region in the second reheating step. On the other hand, if the area ratio of the ferrite phase in the surface layer is less than 80%, a large amount of hard residual consisting of a bainite phase, a pearlite phase, a martensite phase, or a mixed phase thereof will be present. As a result, the hardness of the surface layer increases, and the desired elongation characteristics in the entire thickness cannot be obtained. In addition, the tensile strength may become excessive.
[0049] Here, the area ratio of the ferrite phase in the surface layer refers to the average value of the area ratio of the ferrite phase in the range from the surface to 100 μm below the surface of the thick steel plate. Also, the microstructure in the surface layer refers to the microstructure of the surface layer at two locations taken from any position in the rolling direction of the thick steel plate. Therefore, the steel plate of the present invention is measured for the area ratio of the ferrite phase in the range from the surface to 100 μm below the surface at two locations taken from any position in the rolling direction of the thick steel plate, and the average value is 80% or more. Note that, usually, if the microstructure of the surface layer at two locations taken from any position in the rolling direction of the thick steel plate satisfies the above condition, the thick steel plate satisfies the above condition over the entire length in the rolling direction. Therefore, it can be said that the area ratio of the ferrite phase in the surface layer of the thick steel plate of the present invention is 80% or more over the entire length in the rolling direction. Note that, regarding the upper limit value, the ferrite phase in the surface layer may be 100% in order to ensure the desired strength.
[0050] The remainder of the microstructure of the surface layer other than the ferrite phase is preferably a hard phase, and the hard phase is preferably a pearlite phase or a mixed phase of bainite and pearlite phases. However, since the bainite phase contains island martensite and reduces toughness, the less bainite phase the better, and it is more preferable to have only pearlite phase.
[0051] Structure at 1 / 4 of plate thickness (internal structure of plate thickness) In the thick steel plate of the present invention, the microstructure at the 1 / 4 position of the plate thickness (hereinafter, sometimes simply referred to as "plate thickness interior") contains ferrite phase at an area ratio of 90% or less. In order to suppress excessive increase in strength and decrease in toughness, it is preferable that the microstructure contains ferrite phase at an area ratio of 50% or more. When the microstructure in the plate thickness interior satisfies the above conditions, desired strength and fatigue crack propagation resistance can be obtained. In addition, the average crystal grain size of the ferrite phase is 25 μm or less. When the microstructure in the plate thickness interior satisfies the above conditions, desired toughness can be obtained. It is preferably 23 μm or less, more preferably 20 μm or less. On the other hand, in order to suppress excessive increase in strength and decrease in toughness, the average crystal grain size of the ferrite phase is preferably 3 μm or more.
[0052] Here, the area ratio of the ferrite phase in the thickness direction refers to the average value of the area ratio of the ferrite phase at the 1 / 4 position of the thickness of the thick steel plate. Here, the microstructure in the thickness direction refers to the microstructure in the thickness direction at two locations taken from any position in the rolling direction of the thick steel plate. Therefore, in the thick steel plate of the present invention, the microstructure at the 1 / 4 position of the thickness at two locations taken from any position in the rolling direction of the thick steel plate satisfies the above condition. Note that, as with the structure of the surface layer, if the microstructure in the thickness direction at two locations taken from any position in the rolling direction of the thick steel plate satisfies the above condition, the thick steel plate satisfies the above condition over the entire length in the rolling direction. Therefore, it can be said that the microstructure in the thickness direction of the thick steel plate of the present invention is a ferrite phase with an area ratio of 90% or less and an average grain size of 25 μm or less over the entire length in the rolling direction.
[0053] In the present invention, it is important to disperse the hard phase in the ferrite phase. By dispersing the hard phase in the ferrite phase, fatigue cracks propagating through the ferrite phase bend or branch when they encounter the hard phase. As a result, fatigue crack propagation resistance is improved. If the average interval between the hard phases is 25 μm or more, fatigue crack propagation resistance is deteriorated. Therefore, when dispersing the hard phase in the ferrite phase, it is necessary to make the average interval between the hard phases less than 25 μm. The average interval between the hard phases refers to the distance obtained by measuring the intervals between the hard phases dispersed in the ferrite phase in two observation fields taken from any position in the rolling direction of the thick steel plate and averaging them. Specifically, for example, when the hard phase is composed of bainite and pearlite, the average distance refers to the distance obtained by calculating the distance between all bainite phases and bainite phases, the distance between pearlite phases and pearlite phases, and the distance between bainite phases and pearlite phases. It is preferably less than 20 μm. More preferably, it is less than 10 μm. In addition, since the hard phase needs to be dispersed in the ferrite phase, the average spacing between the hard phases should be more than 0 μm, and is preferably 2 μm or more.
[0054] Moreover, if the hard phase is present in a band shape over the entire surface, it is not preferable because the desired fatigue crack propagation resistance cannot be obtained. Here, the band-shaped structure refers to a structure in which the hard phase is continuously formed over 100 μm or more in the rolling direction when observed at a position of 1 / 4 of the sheet thickness in a plane (L cross section) formed by the rolling direction and the sheet thickness direction of the steel sheet. Therefore, in order to obtain the desired fatigue crack propagation resistance, it is preferable that the hard phase has a major axis of less than 100 μm in the rolling direction. More preferably, it is 25 μm or less. It is preferable that the hard phase has a major axis of 1 μm or more in the rolling direction.
[0055] The remainder of the microstructure within the plate thickness must be a hard phase containing pearlite phase in order to improve fatigue crack propagation characteristics without deteriorating toughness, and the hard phase preferably consists of pearlite phase or a mixed phase of pearlite phase and bainite phase. The bainite phase contains island martensite and reduces toughness. For this reason, it is preferable to make the area ratio of the pearlite phase greater than the area ratio of the bainite phase. The area ratio of the bainite phase is preferably 15% or less. The area ratio of the bainite phase is more preferably 13% or less, further preferably 11% or less, and further preferably 9% or less. The lower limit of the bainite phase may be 0%. The area ratio of the pearlite phase is preferably 5% or more, and preferably 30% or less. In addition, since the martensite phase reduces elongation and toughness, the dispersion of the martensite phase as a hard phase is not preferable, and in particular, the dispersion of the martensite phase alone is even more unfavorable. Here, the remainder of the microstructure within the plate thickness refers to the remainder at 1 / 4 of the plate thickness of the plate at two locations sampled from arbitrary positions in the rolling direction of the plate. That is, the remainder of the microstructure over the entire length of the plate in the rolling direction is a hard phase, including a pearlite phase, and preferably the hard phase is a pearlite phase or a mixed phase of a pearlite phase and a bainite phase, and the hard phase is dispersed in the ferrite phase.
[0056] The microstructures at the surface layer and inside the plate thickness can be evaluated by the method described in the Examples.
[0057] [Total thickness elongation] The total thickness elongation of the thick steel plate is not particularly limited, but is preferably 19% or more when the plate thickness exceeds 16 mm, and 15% or more when the plate thickness is 16 mm or less. In the present invention, it is preferable that the above-mentioned total thickness elongation condition is satisfied at two points taken from any position in the rolling direction of the thick steel plate. Note that, normally, if two points taken from any position in the rolling direction of the thick steel plate satisfy the above-mentioned condition, the thick steel plate satisfies the above-mentioned condition over the entire length in the rolling direction. The total thickness elongation can be measured by the method described in the Examples.
[0058] [Tensile strength] The tensile strength (TS) of the thick steel plate is not particularly limited, but is preferably 490 MPa or more. The upper limit of TS is also not particularly limited, but for example, it is 490 MPa (50 kgf / mm) according to JIS. 2 ) grade, TS should be 610MPa or less. 2 ) grade, the upper and lower limits of TS may be set to 570 MPa and 720 MPa, respectively. In the present invention, it is preferable that the above TS condition is satisfied at two points taken from any position in the rolling direction of the steel plate. Generally, if the above condition is satisfied at two points taken from any position in the rolling direction of the steel plate, the above condition is satisfied over the entire length of the steel plate in the rolling direction. TS can be measured by the method described in the Examples.
[0059] [Toughness] The steel plate of the present invention has excellent toughness as a result of having the above-mentioned composition and microstructure. The toughness of the steel plate of the present invention is not particularly limited, but in the case of a test piece having a thickness of 10 mm, the Charpy absorbed energy vE0 at 0°C, which is one of the indicators of toughness, is preferably 100 J or more, more preferably 130 J or more, even more preferably 150 J or more, and most preferably 270 J or more. In the case of a test piece having a thickness of 5 mm, the Charpy absorbed energy vE0 is preferably 50 J or more. On the other hand, the upper limit of vE0 is not limited, but may be, for example, 400 J or less. Note that vE0 can be measured by the method described in the examples.
[0060] [Fatigue crack propagation characteristics] The steel plate of the present invention has the above-mentioned composition and microstructure, and as a result, has excellent fatigue crack propagation resistance. The fatigue crack propagation rate (da / dN) can be used as an index of fatigue crack propagation resistance. Although the value of the fatigue crack propagation rate is not particularly limited, in the present invention, the fatigue crack propagation rate at ΔK=25 MPa√m is 8.50×10 -8 The fatigue crack propagation rate (da / dN) can be measured by the method described in the Examples.
[0061] Plate Thickness In the present invention, the term "thick steel plate" refers to a steel plate having a thickness of 6 mm or more, in accordance with the usual definition in this technical field. On the other hand, the upper limit of the plate thickness of the thick steel plate in the present invention is not particularly limited and can be any value.
[0062] [Paint film] The steel plate of the present invention may have a coating film on the surface. The coating film is not particularly limited and any coating film can be used.
[0063] The coating film may be, for example, a coating film having a corrosion-resistant undercoat layer, a primer layer, an intermediate coat layer, and a top coat layer in this order. The corrosion-resistant undercoat layer is preferably an inorganic zinc-rich paint formed using an inorganic zinc-rich paint, and more preferably a layer containing an alkyl silicate resin and zinc powder. The inorganic zinc-rich paint is not particularly limited, but an example thereof is SD Zinc 1500 manufactured by Kansai Paint Co., Ltd. The undercoat layer is preferably formed using an epoxy resin paint (epoxy resin coating film). The epoxy resin paint is not particularly limited, but an example thereof is Epomarine HB (K) manufactured by Kansai Paint Co., Ltd. The intermediate coat layer is preferably formed using an intermediate coat paint for fluororesin top coat paint, and more preferably an epoxy resin coating film. The intermediate coat paint for fluororesin top coat paint is not particularly limited, but an example thereof is Ceratect F intermediate coat manufactured by Kansai Paint Co., Ltd., which is a polyamide-cured epoxy resin intermediate coat paint. The top coat layer is preferably formed using a fluororesin top coat paint (fluororesin coating film). The fluororesin topcoat paint is not particularly limited, but an example thereof is Ceratect F(K) topcoat paint manufactured by Kansai Paint Co., Ltd., which is a low-polluting isocyanate-cured fluororesin paint.
[0064] [Structure] By using the steel plate of the present invention in structures such as bridges that are used in outdoor atmospheric corrosive environments, particularly in severe corrosive environments such as at sea or near the coast where there is a large amount of airborne salt, it becomes possible to reduce the maintenance costs and therefore the life cycle costs of such structures, and furthermore, it becomes possible to prevent a decrease in strength characteristics during a fire and ensure high safety.
[0065] [Manufacturing method] The thick steel plate of the present invention is manufactured by sequentially subjecting a steel material having the above-mentioned chemical composition to a heating process, a rolling process, a cooling process after the rolling process, a first reheating process, a first cooling process, a second reheating process, a second cooling process, and a water cooling process.
[0066] Steel Material As the steel material of the present invention, any material having the above-mentioned composition and capable of being hot-rolled can be used, but typically, a steel slab is sufficient. For example, molten steel having the above-mentioned composition can be produced by means of a converter or the like, and can be made into a steel material such as a slab by a casting method such as a continuous casting method. Also, a steel material such as a slab can be made by an ingot casting-splitting rolling method.
[0067] heating process The steel material having the above-mentioned composition is heated to 900 to 1200°C. If the heating temperature is less than 900°C, the deformation resistance of the steel material in the next rolling process increases, the load on the hot rolling machine increases, and hot rolling becomes difficult. Therefore, the heating temperature is set to 900°C or higher. The heating temperature is preferably set to 950°C or higher. On the other hand, if the heating temperature exceeds 1200°C, the reverse transformed austenite becomes coarse, and the crystal grains of the ferrite phase inside the thickness of the finally obtained plate become coarse, resulting in a decrease in toughness. Therefore, the heating temperature is set to 1200°C or lower. The heating temperature is preferably set to 1150°C or lower.
[0068] In addition, when a steel material (slab) is produced by a method such as continuous casting, the slab may be directly subjected to the above heating step without cooling, or may be subjected to the above heating step after cooling. In addition, the heating method is not particularly limited, and for example, the slab may be heated in a heating furnace according to a conventional method.
[0069] Rolling process The heated steel material is then hot-rolled to produce a thick steel plate. In this process, the cumulative rolling reduction is set to 50% or more in order to ensure toughness. If the cumulative rolling reduction is less than 50%, the crystal grains of the ferrite phase inside the plate thickness finally obtained will become coarse, resulting in localized regions of low brittleness, which will make brittle cracks more likely to occur and reduce toughness. There is no particular upper limit, but it is preferably set to 99% or less from the viewpoint of suppressing efficiency reduction due to load restrictions of the rolling mill. Other conditions related to the hot rolling process are not particularly limited.
[0070] Cooling process after rolling Next, the steel plate after the rolling process is cooled. By cooling the steel plate after the rolling process, the crystal grains of the ferrite phase inside the plate thickness can be refined and the toughness can be improved. In the cooling process, it is preferable to cool to room temperature. The cooling can be performed by any method, for example, air cooling or water cooling. However, water cooling is more preferable from the viewpoint of suppressing the coarsening of crystal grains. In addition, there is no particular limitation on the cooling conditions.
[0071] First reheating step In the first reheating step, the steel plate after the cooling step is reheated to a temperature between the Ac3 transformation point and 950°C (first reheating temperature). By reheating to a temperature between the Ac3 transformation point and 950°C in this manner, the microstructure of the entire steel plate is reverse transformed to the austenite phase, and the variation in the microstructure in the rolling direction (longitudinal direction) caused by the deviation in the cooling stop temperature can be eliminated. As a result, the variation in mechanical properties (strength) can be eliminated, and further, the crystal grains of the ferrite phase inside the plate thickness after the first cooling step are also refined, so that the toughness is improved. On the other hand, when the first reheating temperature exceeds 950°C, the crystal grains of the reverse transformed austenite phase grow and become coarse, so that the crystal grains of the ferrite phase inside the plate thickness finally obtained also become coarse, and the toughness is reduced.
[0072] In the first reheating step, it is preferable to heat the material to the first reheating temperature and then maintain the temperature at that temperature. If the holding time exceeds 60 minutes, the crystal grains of the reverse transformed austenite phase grow excessively, and the toughness tends to decrease. On the other hand, if the holding time is less than 10 minutes, the reverse transformation to the austenite phase does not proceed sufficiently, so that the microstructure inside the plate thickness becomes non-uniform, and the toughness deteriorates in part of the steel plate. Therefore, the holding time in the first reheating step is preferably 10 minutes or more and 60 minutes or less.
[0073] First cooling step In the first cooling step, the steel plate after the first reheating step is cooled. By cooling the steel plate after the first reheating step, the crystal grains of the ferrite phase inside the plate thickness finally obtained can be further refined, and the toughness can be further improved. For a steel plate having a plate thickness of 50 mm or less, the cooling in the first cooling step can be performed by any method, for example, air cooling or water cooling, and water cooling is preferable from the viewpoint of suppressing the coarsening of crystal grains. For this reason, the cooling rate is preferably 1°C / s or more, more preferably 20°C / s or more, and even more preferably 40°C / s or more. The upper limit does not need to be particularly limited, but from the viewpoint of effective use of water resources used for cooling, 100°C / s or less is preferable. The cooling stop temperature (first cooling stop temperature) may be lower than the second reheating temperature, and is more preferably 300°C or less and room temperature (20°C) or more. Furthermore, for thick steel plates with a thickness of more than 50 mm, it may be difficult to achieve a cooling rate sufficient to obtain the desired structure inside the plate thickness if air cooling is used in the first cooling step, but water cooling is preferable because it is possible to achieve an average cooling rate of 20°C / s or more with water cooling.
[0074] Second reheating step In the second reheating step, the steel plate after the first cooling step is reheated to a temperature (second reheating temperature) of not less than the Ac1 transformation point and not more than 950° C. The second reheating temperature is preferably lower than the Ac3 transformation point.
[0075] When the second reheating temperature is equal to or higher than the Ac1 transformation point and lower than the Ac3 transformation point, the decarburization reaction specific to the two-phase region progresses, and the area ratio of the ferrite phase in the surface layer can be set to 80% or more. On the other hand, when the second reheating temperature is equal to or higher than the Ac3 transformation point and lower than 950°C, the holding time at the second reheating temperature is set to a short time, so that the reaction in which the ferrite phase in the surface layer generated by the surface decarburization reaction during passage through the two-phase region is reversely transformed into the austenite phase is suppressed, and the area ratio of the ferrite phase in the surface layer can be set to 80% or more. When the second reheating temperature is lower than the Ac1 transformation point, the surface decarburization reaction specific to the two-phase region does not progress, and the area ratio of the ferrite phase in the surface layer is less than 80%. As a result, the hardness of the surface layer increases and the desired elongation characteristics at the entire thickness cannot be obtained. Furthermore, the reverse transformation reaction to the austenite phase does not occur in the inner thickness of the plate, and the grain refinement of the ferrite phase in the inner thickness of the plate does not occur after the second cooling process. As a result, the toughness decreases. On the other hand, if the second reheating temperature is higher than 950°C, the reaction of reverse transformation of the ferrite phase in the surface layer generated by the surface decarburization reaction during passage through the two-phase region to the austenite phase is promoted, and the area ratio of the ferrite phase in the surface layer becomes less than 80%. As a result, the hardness of the surface layer increases and the desired elongation characteristics over the entire thickness cannot be obtained. Furthermore, the austenite phase reverse transformed inside the plate thickness grows and coarsens, resulting in localized regions of low brittleness and reduced toughness.
[0076] In addition, when the second reheating temperature is equal to or higher than the Ac3 transformation point and equal to or lower than 950°C, the grains of the austenite phase inside the plate thickness become coarser than when the second reheating temperature is lower than the Ac3 transformation point, but the toughness does not deteriorate excessively. Furthermore, in this temperature range, the rate of reverse transformation to the austenite phase inside the plate thickness increases. Therefore, the reverse transformation reaction to the austenite phase is completed in a short heating time, and the number of thick steel plates that can be manufactured in a given time increases, improving productivity.
[0077] The Ac1 transformation point can be determined, for example, by the following formula (1). Ac1(℃)=723+29.1×Si-10.7×Mn-16.9×Ni+16.9×Cr…(1) The Ac3 transformation point can be determined, for example, by the following formula (2). Ac3(℃)=961.6-311.9×C+49.5×Si-36.4×Mn+438.1×P-2818×S+12.7×Al-51×C u-29×Ni-8.7×Cr+13.5×Mo+308.1×Nb-140×V+318.9×Ti+611.2×B-969×N…(2) Here, the element symbols in the above formulas (1) and (2) indicate the content (mass %) of each element, and are set to zero when the element is not contained.
[0078] The retention time in the second reheating step will be described below.
[0079] In the second reheating step, it is preferable to heat the steel plate to the second reheating temperature and then hold the temperature. When the second reheating temperature is equal to or higher than the Ac1 transformation point and lower than the Ac3 transformation point, if the holding time is less than 10 minutes, the reverse transformation to the austenite phase does not start over the entire length of the steel plate, and it is difficult to obtain a desired microstructure in the plate thickness after the second cooling step. In addition, in the surface layer, the decarburization reaction does not proceed sufficiently, and it is difficult to obtain a desired microstructure in the surface layer. Therefore, it is preferable to hold the temperature for 10 minutes or more. There is no need to particularly limit the upper limit, but it is preferable to hold the temperature for 120 minutes or less from the viewpoint that long-term heating leads to an increase in the operating costs of maintaining the heating furnace. On the other hand, when the second reheating temperature is equal to or higher than the Ac3 transformation point and lower than 950°C, if the holding time exceeds 30 minutes, the reversely transformed austenite phase grows in the plate thickness, the crystal grains become coarse, and the toughness decreases. In addition, in the surface layer, the reverse transformation to the austenite phase proceeds more, and it is difficult to obtain a desired microstructure in the surface layer. Therefore, it is preferable to hold the temperature for 30 minutes or less. Although there is no particular lower limit, it is preferable to set the lower limit to 5 minutes or more in order to sufficiently advance the phase transformation.
[0080] Second cooling process In the second cooling step, the thick steel plate reheated in the second reheating step is cooled to a second cooling stop temperature of 350 to 600 ° C. In this case, the second average cooling rate is set to 1.5 to 20 ° C. / s. If the second average cooling rate is less than 1.5 ° C. / s, pearlite is generated in a band shape as described above, and the frequency of encounter between the fatigue crack and the pearlite increases, so that the fatigue crack propagation resistance property decreases. Therefore, the second average cooling rate is set to 1.5 ° C. / s or more, and the pearlite phase is dispersed in the ferrite phase. On the other hand, if the second average cooling rate exceeds 20 ° C. / s, the pearlite transformation does not proceed sufficiently in the microstructure inside the plate thickness, and the bainite transformation tends to proceed. Since the bainite contains island martensite, the toughness decreases with an increase in the bainite area ratio. If the cooling rate is 20°C / s or less, the pearlite transformation in the microstructure inside the steel sheet proceeds moderately, and the grain size of the ferrite phase is refined in the process prior to the second cooling process, so that the desired toughness can be obtained. Furthermore, if the cooling rate is 7°C / s or less, the area ratio of the bainite phase becomes smaller than the area ratio of the pearlite phase, and the toughness is further improved. The second average cooling rate is preferably 5°C / s or less, more preferably 4°C / s or less, and even more preferably less than 3°C / s. The average cooling rate can be obtained by measuring the temperature distribution of the steel sheet after cooling using a non-contact type radiation thermometer and calculating the temperature history before and after cooling. In addition, the temperature history from before cooling to after cooling can be constantly measured and calculated using a contact type thermocouple or the like.
[0081] Furthermore, if the second cooling stop temperature is less than 350°C, ferrite will be excessively formed within the plate thickness, softening the entire steel plate and making it impossible to obtain the desired tensile strength. Therefore, the second cooling stop temperature is set to 350°C or higher. On the other hand, if the second cooling stop temperature is more than 600°C, the plate will be quenched with a large amount of untransformed austenite remaining, resulting in the excessive formation of hard bainite and martensite within the plate thickness. As a result, the elongation characteristics throughout the entire thickness will decrease, and the toughness will also decrease. Therefore, the second cooling stop temperature is set to 600°C or lower.
[0082] According to the manufacturing method of the present application, the steel sheet is subjected to a total of three processes of repeating normal transformation and reverse transformation, including the first reheating, the first cooling process from the first reheating, and the second cooling process from the second reheating. The grains become fine by repeating normal transformation and reverse transformation. Therefore, this process is important for refining the grains, and the average grain size of the ferrite phase can be obtained to a desired value.
[0083] water cooling process In the water cooling step, the steel plate after the second cooling step is water-cooled to prevent the formation of band-shaped structures. Therefore, the water cooling temperature is in the range of 350 to 600°C. Water cooling is not particularly limited and can be performed under any conditions, but it is preferable to water-cool the steel plate to a temperature below the Ms point, preferably below 200°C. The Ms point can be calculated, for example, by the following formula (3). Water cooling refers to cooling at an average cooling rate of 20°C / s or more. The upper limit of the average cooling rate is preferably 100°C / s or less. Ms(℃)=517-300×C-11×Si-33×Mn-17×Ni-22×Cr-11×Mo…(3) Here, the element symbols in the above formula (3) indicate the content (mass%) of each element, and are set to zero when the element is not contained.
[0084] The production conditions other than those mentioned above are not particularly limited, but the following conditions are preferable.
[0085] Cooling after water cooling process In the present invention, the cooling method after the water-cooling step is not particularly limited, and any method such as air cooling or water cooling can be used. EXAMPLES
[0086] The effects of the present invention will be specifically described below based on examples, but the present invention is not limited to these examples.
[0087] Molten steel having the composition shown in Table 1 was produced as a steel material (slab). The values of Ac1, Ac3, and Ms shown in Table 1 were calculated using the above-mentioned formulas (1), (2), and (3), respectively.
[0088] Next, the obtained slab was heated (heating step) and hot rolled (rolling step) under the conditions shown in Table 2 to obtain a thick steel plate with a total length of 20 m and a plate thickness shown in Table 2. The thick steel plate was then cooled to room temperature by the cooling method shown in Table 2 (cooling step), reheated to the first reheating temperature shown in Table 2, and held for the holding time shown in Table 2 (first reheating step). Then, it was cooled to the first cooling stop temperature at the first average cooling rate by the cooling method shown in Table 2 (first cooling step). Then, it was reheated to the second reheating temperature shown in Table 2, and held for the holding time shown in Table 2 (second reheating step). Then, it was cooled to the second cooling stop temperature at the second average cooling rate by the cooling method shown in Table 2 (second cooling step). Then, it was subjected to water cooling treatment (water cooling step). In the water cooling step, it was water cooled to 150°C or less.
[0089] The obtained steel plates were evaluated for (1) microstructure, (2) total thickness elongation and tensile strength (TS), (3) fatigue crack propagation properties, (4) toughness, and (5) paint durability. For tests (1) to (4), in order to evaluate the variation in properties in the rolling direction and width direction of the steel plate, test pieces were taken from each of the arbitrary positions in the rolling direction of the steel plate, and the two positions with the largest variation (position 1 and position 2) were evaluated. For test (5), a test piece was taken from an arbitrary position in the rolling direction. The test method is as follows. The above test pieces were taken from a position 100 mm in from the end of the steel plate in the rolling direction.
[0090] (1) Microstructure observation The microstructure was observed according to the following procedure.
[0091] Area ratio of ferrite phase in the surface layer, area ratio of ferrite phase in the thickness direction, area ratio of pearlite phase and bainite phase in the thickness direction First, a test piece for microstructure observation was taken from the obtained thick steel plate so that the observation surface was a cross section perpendicular to the rolling direction (cross section in the plate thickness direction), polished to a mirror surface, and then corroded with an etching solution (nitric acid methanol solution). The specimen was observed from the surface of the steel plate to the 1 / 4 position in the plate thickness direction using an optical microscope (magnification: 400 times) or a scanning electron microscope (magnification: 400 times), and images were taken so that the screen was continuous. Using the obtained microstructure photograph, the phases were identified by image analysis, and (a) the average value of the area ratio of the ferrite phase in the range from the surface to 100 μm below the surface of the thick steel plate, (b) the average value of the area ratio of the ferrite phase at the 1 / 4 position of the plate thickness, the average value of the ferrite grain size obtained by the cutting method described in JIS G 0551, and (c) the area ratio of the pearlite phase and the bainite phase at the 1 / 4 position of the plate thickness were obtained. In the above image, the white part is judged to be the ferrite phase, the black part is the pearlite phase, and the remaining part is the bainite phase. The average spacing between hard phases was calculated by performing image analysis on the above image using Image-J and calculating the distance between edges. Specifically, the phase boundaries in each region of the hard phase, specifically the pearlite phase and the bainite phase, were detected and drawn as edges (contour lines), and the distance between the edges of the closest hard phases (pearlite phase or bainite phase) was measured. The above evaluation was performed for 10 fields of view, and the average value was calculated as the average spacing between the hard phases.
[0092] The size of the hard phase is measured by detecting and drawing the edges (contour lines) of the phase boundaries in each region of the pearlite phase and bainite phase, and measuring the width in the rolling direction.
[0093] The martensite phase was identified based on the pattern of the hard phase in the scanning electron microscope (magnification: 400 times) image taken above.
[0094] The results of the microstructural measurements are shown in Table 3.
[0095] (2) Tensile test Tensile tests were conducted using full-thickness test pieces of JIS Z 2201 No. 1A taken from the width center of the thick steel plate so that the plate width direction coincided with the tensile direction, and the tensile strength (TS) and full-thickness elongation were obtained. A tensile strength of 490 MPa or more was considered to pass. Elongation properties were considered to pass when the plate thickness was 16 mm or less, and 15% or more when the plate thickness was over 16 mm.
[0096] (3) Fatigue crack propagation test A fatigue crack propagation test was conducted using a single-side notched simple tension fatigue test specimen as shown in Figure 1 to evaluate the fatigue crack propagation behavior when the crack propagates in the width direction of the steel plate. The test specimen was a compact tension test specimen taken from the 1 / 4 position of the plate thickness, and the test conditions were in accordance with ASTM E647, a stress ratio of 0.1, a frequency of 10 Hz, and the test was conducted in air at room temperature. Since the purpose of the present invention is to reduce the propagation speed of cracks that occur at welds in welded structures and propagate through steel material, assuming such a situation, tests were conducted with a stress intensity factor range (ΔK) of 10 to 30 MPa√m. The fatigue crack propagation speed at ΔK = 25 MPa√m was 8.50 x 10 -8 m / cycle or less was considered a pass.
[0097] (4) Toughness Charpy impact test pieces were taken from the center of the thickness of the thick steel plate, parallel to the rolling direction (L direction). The thickness of the test piece was 10 mm when the plate thickness was 10 mm or more, and 5 mm when the plate thickness was less than 10 mm. The test was a Charpy impact test conducted at 0°C in accordance with JIS Z 2202, and the absorbed energy vE0 was measured. A test piece with a thickness of 10 mm was considered to have passed if the absorbed energy was 100 J or more. A test piece with a thickness of 5 mm was considered to have passed if the absorbed energy was 50 J or more.
[0098] (5) Paint durability A test piece measuring 70 mm x 50 mm x 5 mmt was taken from the obtained thick steel plate, and the coating durability was evaluated. Specifically, first, the surface of the test piece was shot blasted so that the rust removal degree Sa specified in ISO 8501-1 was 2.5. Next, the test piece was ultrasonically degreased in acetone for 5 minutes, and then air-dried. Next, the following paints (a) to (d) were applied in order to one side of the test piece to form a coating film consisting of a corrosion-resistant base layer, a base coat layer, a middle coat layer, and a top coat layer. The thickness of each layer is also shown below. (a) Anticorrosive base layer: inorganic zinc-rich paint (SD Zinc 1500A manufactured by Kansai Paint Co., Ltd.), thickness: 75 μm (b) Undercoat layer: epoxy resin paint (Epomarine HB(K) manufactured by Kansai Paint Co., Ltd.), thickness: 120 μm (c) Intermediate layer: intermediate coating for fluororesin topcoat (Kansai Paint Co., Ltd. Ceratect F intermediate coating), thickness: 30 μm (d) Topcoat layer: Fluororesin topcoat paint (Kansai Paint Co., Ltd. Ceratect F topcoat paint), thickness: 25 μm After the coating was formed, the other surface and end surface of the test piece were sealed with a solvent-based epoxy resin paint, and further coated with a silicone-based sealant. A linear cut of width 1 mm and length 40 mm reaching the steel substrate was made in the center of the coating formed on the test piece as an initial defect. Then, a corrosion test was carried out under the following conditions.
[0099] Corrosion Testing The amount of artificial sea salt attached to the surface of the test piece was 6.0 g / m 2 A solution of artificial sea salt diluted with pure water to a specified concentration was sprayed onto the test piece to adhere the artificial sea salt to the test piece. Next, a corrosion test was carried out using this test piece, repeating the following cycle (total of 8 hours) for 1200 cycles. The artificial sea salt was applied once a week. (cycle) Condition 1: Temperature 60℃, relative humidity 35%, retention time 3 hours · Transition from Condition 1 to Condition 2: 1 hour Condition 2: Temperature 40℃, relative humidity 95%, retention time 3 hours · Transition from Condition 2 to Condition 1: 1 hour After the corrosion test, the paint blister area from the initial defect was measured and used as an index of paint durability. 2 The following were considered to be acceptable:
[0100] The measurement results are shown in Table 4. As can be seen from the results, in the examples that satisfy the conditions of the present invention, thick steel plates having elongation characteristics across the entire thickness, fatigue crack propagation resistance, toughness, and coating durability were obtained. On the other hand, in the comparative examples that do not satisfy the conditions of the present invention, at least one of the strength characteristics, elongation characteristics across the entire thickness, fatigue crack propagation rate, toughness, and coating durability was inferior in at least one of the two positions evaluated in the rolling direction of the thick steel plate.
[0101] [Table 1]
[0102] [Table 2]
[0103] [Table 3]
[0104] [Table 4]
Claims
1. In mass percent, C: 0.05-0.20%, Si: 0.01 to 0.50%, Mn: 0.50-2.00%, P: 0.05% or less, S: 0.02% or less, W: 0.005-1.00% and Sn: 0.005-0.500%, Sb: Contains at least one of 0.005 to 0.200%; The balance has a composition consisting of Fe and unavoidable impurities, The microstructure is In the thickness direction, the area from the surface to 100 μm below the surface contains a ferrite phase of 80% or more by area ratio, and At the 1 / 4 plate thickness position, Contains a ferrite phase having an area ratio of 90% or less and an average crystal grain size of 25 μm or less, The balance of the steel plate is a hard phase, the hard phase is dispersed in a ferrite phase, the hard phase includes a pearlite phase, and the average spacing between the hard phases is less than 25 μm.
2. The composition further comprises, in mass%, Cu: 0.01 to 1.00%, Ni: 0.01-1.00%, Cr: 0.01-1.00%, Mo: 0.01-1.00%, V: 0.005-0.100%, Ti: 0.005 to 0.10%, B: 0.0001 to 0.0050%, Ca: 0.0001-0.020%, Mg: 0.0001 to 0.020%, and The steel plate according to claim 1, further comprising one or more selected from the group consisting of REM: 0.0001 to 0.020%.
3. 2. The steel plate according to claim 1, wherein the hard phase is composed of a pearlite phase or a mixed phase of pearlite and bainite, and the area ratio of the pearlite phase in the mixed phase is larger than the area ratio of the bainite phase.
4. 3. The steel plate according to claim 2, wherein the hard phase is made of a pearlite phase or a mixed phase of pearlite and bainite, and the area ratio of the pearlite phase in the mixed phase is larger than the area ratio of the bainite phase.
5. The steel plate according to any one of claims 1 to 4, which has a coating film on its surface.
6. The coating film includes a corrosion-resistant undercoat layer, a primer layer, a midcoat layer, and a topcoat layer, 6. The thick steel plate according to claim 5, wherein the anticorrosive undercoat layer is made of inorganic zinc-rich paint, the undercoat layer is made of epoxy resin paint, the intermediate coat layer is made of intermediate paint for a fluororesin top coat paint, and the top coat layer is made of a fluororesin top coat paint.
7. A structure formed using the thick steel plate according to any one of claims 1 to 4.
8. A structure formed using the thick steel plate according to claim 5.
9. A structure formed using the thick steel plate according to claim 6.
10. The structure according to claim 7, wherein the structure is a bridge.
11. The structure of claim 8, wherein the structure is a bridge.
12. The structure of claim 9, wherein the structure is a bridge.
13. A method for manufacturing a thick steel plate according to claim 1 or 2, A heating step of heating a steel material having the above-mentioned composition to 900 to 1200°C; a rolling step of subjecting the steel material heated in the heating step to hot rolling at a cumulative rolling reduction rate of 50% or more to obtain a thick steel plate; A cooling step after the rolling step of cooling the thick steel plate; A first reheating step in which the steel plate cooled in the cooling step after the rolling step is reheated to a first reheating temperature of the Ac3 transformation point or higher and 950 ° C. or lower; A first cooling step of cooling the steel plate reheated in the first reheating step; A second reheating step of reheating the steel plate cooled in the first cooling step to a second reheating temperature of the Ac1 transformation point or higher and 950 ° C. or lower; A second cooling step of cooling the steel plate reheated in the second reheating step to a second cooling stop temperature of 350 to 600 ° C. at an average cooling rate of 1.5 to 20 ° C. / s; a water cooling step of water cooling the steel plate cooled in the second cooling step; A method for manufacturing a thick steel plate having the above structure.
14. The method for producing a steel plate according to claim 13, wherein an average cooling rate in the second cooling step is 1.5 to 7 ° C. / s.
Citation Information
Patent Citations
Steel for coating excellent in durability of coating film and its production
JP2000169939A
Steel material excellent in corrosion resistance
JP2013166992A
Refining high tension thick steel and production method thereof
JP2015193917A
Thick steel sheet and manufacturing method of thick steel sheet
JP2019026927A
Structural steel excellent in fatigue crack propagation characteristics and coating durability, and method for producing the same
JP2020164952A